Long non-coding RNA FAM99A modulated YAP1 to affect trophoblast cell behaviors in preeclampsia by sponging miR-134-5p - Xu,Bingnv (2020)
Preeclampsia (PE) is a complex pregnancy syndrome. Convincing evidence indicates that long non-coding RNAs (lncRNAs) are involved in the pathogenesis of PE. This research mainly investigated the mechanism of family with sequence similarity 99 member A (FAM99A) in PE. The expressions of FAM99A, miR-134-5p, and YAP1 were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Cell apoptosis, migration, and invasion were detected by flow cytometry or transwell assay. The interaction between miR-134-5p and FAM99A or YAP1 was confirmed by dual-luciferase reporter assay. The protein expression of YAP1 was determined by western blot assay. FAM99A and YAP1 were significantly up-regulated, and miR-134-5p was significantly down-regulated in PE tissues (n=30). miR-134-5p was verified as a candidate of FAM99A and YAP1. FAM99A promoted cell metastasis, but reduced apoptosis in HTR8/SVneo cells by regulating miR-134-5p. miR-134-5p down-regulated YAP1 expression to suppress cell metastasis, while it induced apoptosis in HTR8/SVneo cells. FAM99A positively modulated YAP1 expression by sponging miR-134-5p. FAM99A modulated YAP1 to accelerate cell migration and invasion, and inhibited cell apoptosis in PE cells by sponging miR-134-5p. The novel regulatory network may shed light on the pathogenesis of PE.